The 30-year evolution of motor vehicle road injuries: Can the future come from the shadows? - Songxiahe Zhao; Zhongjiang Lan; Jinrui Lin; Shihu Kan; Yanliang Jiao; Lei Chen; Yibin Du (PLoS ONE, 2026)
Background This study examines temporal changes from 1990 to 2021 in the burden of vertebral fractures (VFs) attributable to motor vehicle road injuries (MVRIs), with a particular focus on age- and sex-specific patterns in China and India. These national trends are compared with global patterns to better understand population distribution characteristics and injury mechanisms underlying this public health challenge. Methods Data were obtained from the 2021 Global Burden of Disease (GBD) study. Crude rates and age-standardized rates (ASRs) of incidence, prevalence, and years lived with disability (YLDs) for MVRI-related VFs were estimated. Joinpoint regression was applied to assess temporal trends, while age–period–cohort (APC) modeling was used to disentangle the independent effects of age, calendar period, and birth cohort. Results From 1990 to 2021, the global age-standardized incidence rate (ASIR) of MVRI-related VFs declined by 48.8%, with an average annual percentage change (AAPC) of −1.839% (95% confidence interval [CI], −1.869 to −1.808). In contrast, China showed no significant reduction in ASIR (AAPC = −0.478%, 95% CI, −0.531 to −0.426), whereas India demonstrated minimal variation over the study period (AAPC = −0.013%, 95% CI, −0.054 to 0.028). Regional analyses revealed heterogeneous drivers of disease burden. In China, period effects during 2000–2021 were strongly associated with elevated risk among males aged 20–40 years, likely reflecting hazardous driving behaviors, while cohort effects were most prominent among individuals born between 1980 and 1990. Conversely, individuals older than 60 years experienced an increasing burden, potentially related to osteoporosis and rapid motorization. Across all regions, males consistently exhibited higher ASIRs, age-standardized prevalence rates (ASPRs), and YLD rates than females, with the greatest sex disparities observed among younger males in China. Conclusion The persistently high burden of MVRI-related VFs in China, which diverges from declining trends observed in countries with a high sociodemographic index (SDI), highlights the need for targeted prevention strategies. Interventions should prioritize behavioral risk reduction in younger male populations and address age-related biomechanical vulnerability in older adults. In India, strengthening road safety enforcement and trauma care infrastructure remains essential. These findings underscore the heterogeneous demands for road injury prevention in China and India and provide evidence to support more effective allocation of public health resources.